Overcoming challenges in glioblastoma treatment: targeting infiltrating cancer cells and harnessing the tumor microenvironment - Chiariello, Mario; Inzalaco, Giovanni; Barone, Virginia; Gherardini, Lisa (Frontiers in Cellular Neuroscience, 2023)
Glioblastoma (GB) is a highly malignant primary brain tumor with limited treatment options and poor prognosis. Despite current treatment approaches, including surgical resection, radiation therapy, and chemotherapy with temozolomide (TMZ), GB remains mostly incurable due to its invasive growth pattern, limited drug penetration beyond the blood-brain barrier (BBB), and resistance to conventional therapies. One of the main challenges in GB treatment is effectively eliminating infiltrating cancer cells that remain in the brain parenchyma after primary tumor resection. We've reviewed the most recent challenges and surveyed the potential strategies aimed at enhancing local treatment outcomes.